Thermal stress analysis of dry friction clutches - Abdullah, Oday Ibraheem; Schlattmann, Josef; Jobair, Hussein; Beliardouh, Nasser Eddine; Kaleli, Hakan (EMERALD GROUP PUBLISHING LTD, 2020)
Purpose The purpose of this paper is to present an approach to compute accurately the distributions of the frictional heat generated, contact pressure and thermal stresses at any instant during the sliding period (heating phase) of the single-disc friction clutch system works in the dry condition and the complex interaction among them. Design/methodology/approach Numerical work was achieved using the developed elastic and thermal finite element models (axisymmetric models) to simulate the engagement of the single-disc friction clutch system. Findings The change of distribution of contact pressure during the sliding period (heating phase) affects significantly the magnitude and distribution of the produced thermal stress. The high local heat generated appeared in the contacting surfaces because of the non-uniformity of the distribution of contact pressure during the heating phase (sliding time) and this will dramatically increase the thermal stresses. Originality/value Sequentially coupled thermal-mechanical approach was developed to investigate the thermal stresses problem in automotive clutches under dry conditions. This approach is considered a promising approach to investigate the effect of material, sliding time, torque function, etc., on the thermal stresses of different types of friction clutch.
Keywords: Dry sliding; Finite element model; Contact temperature; Contact mechanics; Clutch; Thermo-mechanical coupling; Engineering